Pengaruh Tingkat Pemahaman Wajib Pajak, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak - Ninik Khuzaimah; Sigit Hermawan (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2018)
This research aims to analyze the influence taxpayer level of understanding, taxpayer awareness, and tax penalties against tax compliance individual taxpayers conducting business ( Studies in KPP Pratama “X”). The analytical tool used is lists the questionnaire, data collection in the form of test validity and reliability testing. Hypothesis in this study is that there are influences the taxpayer level of understanding, taxpayer awareness, and tax penalties agains tax compliance individual taxpayer conducting business. To test this hypothesis used data analysis tools such as multiple linear regressio.The results obtained by test validity indicates that all of the questions on the questionnaire is valid. To test reliability of all the variables declared reliable and based on hypothesis test based on the F test, t test, and the coefficient of determination showed relationship between the taxpayer level of understanding, the taxpayer awareness, and tax penalties agains tax compliance individual taxpayer conducting business.Keywords: Understanding, Awareness, Tax Penalties, Compliance.